Sintesis dan Karakterisasi BaSrAl4O8, BaSrAl3FeO8, dan BaSrAl2Fe2O8 - Darwin Ismail; Ismunandar Ismunandar (Institut Teknologi Bandung, 2004)
BaSrAl4O8, BaSrAl3FeO8 and BaSrAl2Fe2O8 oxides have been synthesized and their crystal structures type were determined by XRD diffraction. The diffraction patterns were very close to that of BaSrGa4O8, which has space group P63 (No. 173). All of the compounds have AlO4 tetrahedra (as GaO4), form the six-membered rings sharing corners, and the Ba and Sr atoms occupy large cavities of the six-member rings. Fe atoms possibly replace Al atom in the structure. From Proszki analysis in a hexagonal crystal system and P63 space group (No.173), the obtained cell parameters, a and c for BaSrAl4O8, BaSrAl3FeO8 and BaSrAl2Fe2O8 were successively as follows (8.984(2), 8.625(3)) Ã ; (10.377 (4), 8.619(5)) Ã ; and (10.454(3), 9.140(3)) Ã . Based on ferroelectric properties obtained from RT-66A oscilloscope instrument, only BaSrAl3FeO8 compound exhibited a significant hysteresis loop pattern.